Permainan Sortir Berbasis Loose Parts sebagai Strategi Pengembangan Kemampuan Klasifikasi Anak Usia Dini - Darmaji, Talitha Widad Sabrina; Setiawan, M.Hery Yuli; Widjanarko, Paulus (Kartika: Jurnal Studi Keislaman, 2026)
Write This study was motivated by the low classification ability of children aged 5–6 years at TK Mumtazul Ilmi Surakarta. Classification ability is an important part of cognitive development that needs to be stimulated from an early age through learning activities that are appropriate to children's characteristics. This study aims to improve children's classification ability through the implementation of a treasure sorting game based on loose parts. This study employed a Classroom Action Research (CAR) approach conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were children aged 5–6 years at TK Mumtazul Ilmi Surakarta. Data were collected through observation, interviews, and documentation. Data analysis was carried out using qualitative and quantitative descriptive approaches by examining the improvement of children's classification ability in each cycle. The results showed that the implementation of a treasure sorting game based on loose parts significantly improved children's classification ability. This improvement was indicated by children's ability to group objects based on color, shape, size, and type, as well as increased activeness and independence during the learning process. Therefore, the treasure sorting game based on loose parts is effective as an alternative learning strategy to improve early childhood classification ability